Deposição de sementes de soja em diferentes pressões de vácuo e consumo de combustível - Lauriano, Sidnei Marcelino [UNESP]; de Sousa, Saulo Fernando Gomes [UNESP]; Dias, Patrícia Pereira [UNESP]; Correia, Tiago Pereira da Silva; Silva, Paulo Roberto Arbex [UNESP] (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2017)
In pneumatic precision seeders, the regularity in seeds deposition is essential for a proper sowing process. Thus, the aim of this study was to verify the accuracy in the soy beans seed capturing in different vacuum pressures (3.5 kPa; 4.0 kPa; 5.0 kPa; 5.5 kPa and 6.0 kPa), the seed distribution in the seed lines as well as the fuelconsumption in the tractor-seed set. The experiment was carried out at the College of Agronomy – FCA/UNESP, Botucatu-SP. The outline was random blocks, in subplots layout banded of 30 × 3.15 m, with four replicates per treatment. A tractor-seeder set was used to collect the sample of fuel consumption and seed population. The real population of seed was collected in plastic bags fastened to the end of the conductor pipe, obtaining the population of the 5 central lines of the seeders. The acquisition of the fuel consumption data for each plot, was carried out using a flow meter. Thus, it was observed that the seeder distribution on the vacuum pressure at 3.5; 4.0 and 5.5 kPa decreased in the farthest lines when compared to the central lines. For the hourly fuel consumption, per area and also for the deposition of seeds the regularity in the distribution of seeds is affected when there is vacuum pressure below 5.0 kPa and, consequently, highest consumption. For soybean sowing, seeds having the characteristics described in this study, it is recommended to use vacuum pressure of 6.0 kPa. As a result, this vacuum pressure leads to the lowest fuel consumption per hour, 11.49 L h¯¹ and worked area, 7.35 L ha¯¹.
Seeder performance under different pressures of vaccum and fuel consumption to soybean seeds
Keywords: Glycine max; Mechanization; Plantability